Perfil socioeconômico, físico, profissional e de saúde geral dos fisioterapeutas que atuam com terapia manual no estado de Sergipe - Gois, Diego Silva (2022)
Introduction: Studies on the profile of health professionals acquire relevance for the implementation of national health policies, since they enable health agencies, educational institutions and professional bodies to plan care and educational actions. In physiotherapy, the reality of the performance of physical therapists working with Manual Therapy (TM) is still little studied. Objectives: To analyze the socioeconomic, physical, professional and general health profiles of physiotherapists from Sergipe who work with MT. Methods: A descriptive, cross-sectional observational study was carried out with physical therapists in the state of Sergipe. Participants who signed the informed consent form digitally, aged between 18 and 59 years, from the State of Sergipe and who did not have implications for CREFITO-17 were included. Participants received the invitation and link to the survey carried out on Google Forms via email or on social networks, using the snowball method. In addition, the researchers carried out the dissemination of the research using informative arts and a link to the questionnaires. The sociodemographic data questionnaire, the Physical Therapist Socioeconomic and Professional Profile Questionnaire, the Nordic Musculoskeletal Questionnaire and the General Health Questionnaire-12 were used. Results: Data were collected from a total of 50 physical therapists in the state of Sergipe who worked with MD. Of these, 56% were female, 56% were single and 32% lived in the city of Itabaiana. 82% were aged between 21 and 35 years, 40% had 3 to 4 Minimum Wage (MW) and 54% were self-employed. The majority, 72%, did not have a specialty recognized by COFFITO. 98% use Manual Myofascial Release and 78% Neural Mobilization, 58% reported neck pain/tingling in the last 12 months and 64% were in good general health. Conclusion: The study data suggest that there is a predominance of female professionals, salary range between 3 and 4 MW, low use of the International Classification of Functioning, Disability and Health, a high prevalence of body regions affected by musculoskeletal disorders and good health. of general health among physiotherapists in the state of Sergipe who work with MD.